Perencanaan Sistem Penyediaan Air Bersih (SPAM) Desa Kampung Delima Kecamatan Curup Timur Kabupaten Rejang Lebong - Samsul Huda; Rezi Munizar (Journal of Science, Technology, and Innovation, 2026)
The availability of clean water that meets standards for quality, quantity, and continuity is a strategic necessity for the development of basic infrastructure in rural communities. This study aims to plan a Clean Water Supply System (SPAM) for Kampung Delima Village, East Curup Subdistrict, Rejang Lebong Regency, through an analysis of water needs, distribution network design, and evaluation of the system’s hydraulic performance. The study employed an empirical approach involving the collection of topographic data, water source characteristics, and demographic data, which were then analyzed using geometric projection methods, water demand standards from the Directorate General of Public Works, and piping network simulations using EPANET 2.2. The results show that the population in 2046 is projected to reach 3,250 people, with an average water demand of 4.13 liters/second and a peak hourly flow rate of 6.19 liters/second. The system was designed using a gravity-fed method with a reservoir capacity of 71.5 m³ and an HDPE pipeline network. Hydraulic simulations show that residual pressure and flow velocity meet technical service criteria. This study produced an adaptive, efficient, and sustainable drinking water supply system design suited to the characteristics of rural areas.